Solvent-mediated –C = N chemodosimetry and proton transfer signalling: sensing of hypochlorite ion from ppm to ppb level - Wasseem Akbar; Erum Gull Naz; Masood Ayoub Kaloo (Journal of Taibah University for Science, 2025)
A novel furfural-DAMN Schiff base molecule (3) was designed, synthesized and characterized. The extensively conjugated Π-DA molecule was explored as a novel receptor for hypochlorite (OCl-) sensing. A hypochlorite anion induced structural modulation in 3 and, in turn, a prompt and visual signal was deciphered. The dual-channel approach was mediated via the tuning of solvents. From THF to DMSO, -C = N chemodosimetry was reconciled to proton transfer signalling, (PTS) between –NH2 and OCl-. The PTS resulted in rapid and nanomolar level detection of OCl- in an aqueous environment.